Non-typical distant metastases of non-small cell lung cancer – a case report - Ciszewski, Paweł; Skrzypczak, Mariusz; Chorąży, Zofia; Tyczka, Joanna; Sawicz, Krystyna; Nadolski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2007)
Lung cancer is the most common cause of cancer mortality in men and the fourth most common in women. The most frequent location of distant metastases are: the lung, pleura, liver, suprarenal gland, brain, bones, pericardium and subcutaneous tissue. Others locations of distant metastases are very rare. This case report presents a patient with non-small cell lung cancer who successfully underwent upper left lobectomy and who on post-operation day 7 required partial resection of the small bowel secondary to perforation. This perforation was caused by a metastasis of non-small cell lung cancer. Our paper confirms the fact that distant metastases of non-small cell lung cancer also occurs in atypical places. The late detection of these metastases can cause significant problems. In the light of this case report we want to suggest that an extended diagnostic regimen should be done in all patients with non-small cell lung cancer before the surgical operation.